Direct nematicidal effects of methyl jasmonate and acibenzolar-S-methyl against Meloidogyne incognita. Issue 10 (19th May 2017) - Schouteden, Nele; Lemmens, Eline; Stuer, Nina; Curtis, Rosane; Panis, Bart; De Waele, Dirk
Abstract: The aim of this study was to examine the nematicidal properties of two defence inducers against the root-knot nematode Meloidogyne incognita . A direct-contact bioassay was applied to evaluate the nematicidal effects of acibenzolar-S-methyl (ASM) and methyl jasmonate (MEJA) on second-stage juveniles (J2). Nematodes were incubated in different concentrations of these compounds, and the numbers of immobile nematodes were counted after 24 and 48 h post incubation. Tap water was then added to verify whether the nematodes recovered or remained dead at 72 h. The percentage of dead nematodes was used as indicator for the toxicity of the different solutions. Our results show that ASM, in the formulation of Bion®, and MEJA have nematicidal properties. Abstract :